THE EFFECT OF THE COVID-19 PANDEMIC ON PIETY AND SOCIAL SOLIDARITY OF CATHOLIC PEOPLE IN PONTIANAK ARCHDIOCESE - Kristianus; Laurentius Prasetyo; Mikael Dou Lodo (Bajang Institute, 2022)
This research was motivated by the Covid-19 pandemic that struck the world from March 2020 until today. This pandemic has changed the religious ritual of the Catholic religion around the world from the model of Mass congregation at church to online mass congregation at their homes. This mass congregation service at home indeed changed social interaction patterns. This research aims to investigate whether people's piety and social solidarity also changed with the mass service at home. By combining qualitative and quantitative methods during the last five months, this research finally found that, on the contrary, people's piety and social solidarity improved. It turns out that they are far more religious in their lives and very care about the catholic follower's life and other religious believers. This research has also made the church conduct paradigm reform in serving the people. The church has conducted a new kind of service in this New Normal era, i.e., Profilingcustomers. The church has studied their served people thoroughly. How is their profile, what do they need, and their expectation? The church has set customer focus, friendly, consistent, and continuous improvement. It is an effort to establish the people to the new performance style. The church is expected to keep on formulating new ways to overcome the shock of appreciation of faith due to this pandemic. In life, faith always has ups and downs; that is a portrait of human nature. This era is uncertain, but people will survive and live on. We are looking at the new face of the church, especially regarding piety and social solidarity of the people.